Association of tyrosine with insulin resistance in hepatitis C virus‐related chronic liver disease. Issue 10 (27th August 2013) - Oono, Takashi; Yamasaki, Takahiro; Zaitsu, Junichi; Saeki, Issei; Iwamoto, Takuya; Harima, Yumiko; Marumoto, Yoshio; Hidaka, Isao; Urata, Yohei; Ishikawa, Tsuyoshi; Takami, Taro; Segawa, Makoto; et al.
<x xml:space="preserve">Abstract</x> Aim Insulin resistance (IR) increases during the early stages of hepatitis C virus (HCV)‐related chronic liver disease and is a sign of poor prognosis as well as a risk factor for hepatic fibrosis and hepatocellular carcinoma. We aimed to determine the factors affecting IR in HCV‐related chronic liver disease. Methods We retrospectively examined 71 patients with HCV‐related chronic liver disease and analyzed various parameters, including amino acids, as possible predictors of IR. IR was assessed using the Homeostasis Model of Assessment – Insulin Resistance (HOMA‐IR). Amino acids were assayed by examining branched‐chain amino acids (BCAA), tyrosine level, and the ratio of BCAA to tyrosine level (BTR). Results HOMA‐IR was significantly correlated with body mass index, platelet count, prothrombin time, hemoglobin, total bilirubin, total protein, albumin, total cholesterol, fasting glucose, BTR (r = −0.46, P = 0.0001) and tyrosine (r = 0.55, P < 0.0001). However, BCAA were not significantly correlated with HOMA‐IR (r = −0.21, P = 0.082). In multivariate analysis, only two factors were identified as independent parameters contributing to a HOMA‐IR of 2.5 or more: total cholesterol (odds ratio [OR], 6.511; 95% confidence interval [95% CI], 1.554–27.284; P = 0.010) and tyrosine (OR, 4.839; 95% CI, 1.087–21.549; P = 0.039). Conclusion Serum tyrosine levels may be associated with IR in patients with HCV‐related chronic liver disease.